Phosphoproteomic and Metabolomic Profiling Uncovers the Roles of CcPmk1 in the Pathogenicity of Cytospora chrysosperma - Lu Yu; Yuchen Yang; Dianguang Xiong; Chengming Tian (Microbiology Spectrum, 2022)
ABSTRACT Pmk1, a highly conserved pathogenicity-related mitogen-activated protein kinase (MAPK) in pathogenic fungi, is phosphorylated and activated by MAP2K and acts as a global regulator of fungal infection and invasive growth by modulating downstream targets. However, the hierarchical CcPmk1 regulatory network in Cytospora chrysosperma, the main causal agent of canker disease in many woody plant species, is still unclear. In this study, we analyzed and compared the phosphoproteomes and metabolomes of ΔCcPmk1 and wild-type strains and identified pathogenicity-related downstream targets of CcPmk1. We found that CcPmk1 could interact with the downstream homeobox transcription factor CcSte12 and affect its phosphorylation. In addition, the ΔCcSte12 displayed defective phenotypes that were similar to yet not identical to that of the ΔCcPmk1 and included significantly reduced fungal growth, conidiation, and virulence. Remarkably, CcPmk1 could phosphorylate proteins translated from a putative secondary metabolism-related gene cluster, which is specific to C. chrysosperma, and the phosphorylation of several peptides was completely abolished in the ΔCcPmk1. Functional analysis of the core gene (CcPpns1) in this gene cluster revealed its essential roles in fungal growth and virulence. Metabolomic analysis showed that amino acid metabolism and biosynthesis of secondary metabolites, lipids, and lipid-like molecules significantly differed between wild type and ΔCcPmk1. Importantly, most of the annotated lipids and lipid-like molecules were significantly downregulated in the ΔCcPmk1 compared to the wild type. Collectively, these findings suggest that CcPmk1 may regulate a small number of downstream master regulators to control fungal growth, conidiation, and virulence in C. chrysosperma. IMPORTANCE Understanding the pathogenic mechanisms of plant pathogens is a prerequisite to developing effective disease-control methods. The Pmk1 MAPK is highly conserved among phytopathogenic fungi and acts as a global regulator of fungal pathogenicity by modulating downstream transcription factors or other components. However, the regulatory network of CcPmk1 from C. chrysosperma remains enigmatic. The present data provide evidence that the core pathogenicity regulator CcPmk1 modulates a few downstream master regulators to control fungal virulence in C. chrysosperma through transcription or phosphorylation and that CcPmk1 may be a potential target for disease control.